SunSketcher: a Citizen Science network project for the heliophysics big year - Emslie, A. Gordon; Hudson, Hugh S.; Arbuckle, Greg; Galloway, J. Michael; Peden, Travis; May, Starr; Ferguson, Tameka; Miller, Kelly; Cline, Tabitha; Sawant, Shikha; Florence, Andrea; Gabbard, Kelcee; et al. (Frontiers in Astronomy and Space Sciences, 2026)
SunSketcher is an innovative program of eclipse observations that utilizes a network of smartphones along the path of totality to identify and geolocate the precise contact times via their definitive signature–Baily’s Beads–and hence place meaningful constraints on the shape of the solar disk, in particular its oblateness. The common availability of GPS data for modern smartphones makes such an experiment possible. For the 2024 total solar eclipse in North America (a featured element of the Heliophysics Big Year), our program saw the successful development of the necessary smartphone app by a diverse team of undergraduate students at Western Kentucky University. The smartphone images per se are of rather low quality and not of first-order importance; the primary measurement is instead the precisely timed photometry during the second and third contacts, when the limbs of the Sun and Moon are nearly congruent and the Baily’s Beads just appear. The app was downloaded by about 40,000 volunteers scattered along the eclipse path, from whom the program obtained about 100 GB of science-quality data. This article describes the status of our ongoing analysis of these data.